Impact of N-acetylcysteine (NAC) and calcium hydroxide intracanal medications in primary endodontic infection: a randomized clinical trial - Martinho, Frederico C.; Corazza, Bruna J. M. [UNESP]; Khoury, Rayana D. [UNESP]; Orozco, Esteban I. F. [UNESP]; Toia, Cassia C. [UNESP]; Machado, Felipe P. [UNESP]; Valera, Marcia C. [UNESP] (Springer Nature, 2022)
Objectives: This RCT investigated the impact of N-acetylcysteine (NAC) and calcium hydroxide [Ca(OH)2] intracanal medications (ICMs) in primary endodontic infection with apical periodontitis (PEIAP). Materials and methods: Thirty-six teeth with PEIAP were randomly divided into groups according to the ICM: NAC, Ca(OH)2 + saline solution (SSL), and Ca(OH)2 + 2% chlorhexidine-gel (2% CHX-gel) (all, n = 12). Root canal samples (RCSs) were collected before (s1) and after instrumentation (s2) and after 14 days of ICM (s3). Chemomechanical preparation (CMP) was performed with a Reciproc file and 2.5% NaOCl. Checkerboard DNA–DNA hybridization was used to assess 40 target bacteria species. Results: At s1, bacterial DNA was detected in 100% of RCSs (36/36). All 40 bacterial species were found in PEIAP. The mean number of species per RCS was 17.92 ± 13.18. The most frequent bacteria were S. mitis (65%), E. nodatum (63%), E. faecalis (63%), F. nucl sp vicentii (58%), T. forsythia (58%), and F. periodonticum (56%). CMP reduced the mean number of species per RCS to 6.8 ± 2.36 (p < 0.05). At s3, the intragroup analysis revealed a broader antimicrobial activity for Ca (OH)2 + 2% CHX-gel and NAC than Ca(OH)2 + SSL (p < 0.05). NAC eliminated 8/12 bacteria species resistant to both Ca (OH)2 ICMs, including P. micra, P. nigrescens, T. denticola, A. israelii, P. endodontalis, P. acnes, C. ochracea, and E. corrodens. Conclusions: Ca (OH)2 + 2% chlorhexidine gel (2% CHX gel) showed a greater bacterial elimination over the number of bacterial species; however, NAC eliminated 8/12 bacteria species resistant to both Ca (OH)2 ICMs (RBR-3xbnnn). Clinical relevance: The use of intracanal medication with a broad antimicrobial activity can optimize root canal disinfection. Ca(OH)2 + 2% CHX gel and NAC showed a broader antimicrobial activity than Ca(OH)2 + SSL against endodontic pathogens in primary root canal infection. Trial registration: Brazilian Registry of Clinical Trials (REBEC), No. RBR-3xbnnn.
Keywords: Bacteria; Calcium hydroxide; Intracanal medication; N-acetylcysteine; NAC; Root canal